MEDICAL LACUNARS OF THE UZBEK LANGUAGE (Web of Teachers: Inderscience Research, 2023)
This article is devoted to external medical lacunar units in the Uzbek language and their application in the field of medicine. The author of the article referred to scientific-theoretical sources in Uzbek, Russian, English, French, German and other foreign languages, used them on an analytical basis and revealed the specific features of external medical lacunae. Especially, the fact that the article uses specific linguistic methods of mutual comparison of medical terms increases its theoretical and practical importance. Also, the article focuses on the emergence, development and importance of lacunar units today. Therefore, in this article, lacunar units in medical terms are identified, and their meaning between the Uzbek language and other languages, that is, as an interlingual phenomenon, is highlighted.